Molecular detection, genetic and phylogenetic analysis of trypanosome species in Umkhanyakude district of Kwzulu-Natal Province, South Africa - Taioe, Moeti Oriel (University of the Free State, 2013)
African animal trypanosomiasis (AAT) is a disease caused by haemoparasites of the genus Trypanosoma and its vectors are tsetse flies of the genus Glossina which are endemic to the African continent. In South Africa the disease is restricted to the north eastern parts of KwaZulu-Natal Province and it is transmitted to susceptible vertebrate hosts by Glossina brevipalpis and G. austeni. The current study aimed at determining the prevalence, genetic diversity and the phylogenetic position of the South African trypanosome species in the north eastern KwaZulu-Natal as well as determining preferred feeding host by tsetse flies from their blood meal. A total of 296 blood samples were collected from the north eastern parts of KwaZulu-Natal Province whereby 137 were from cattle; 101; 9; 49 were from goats, sheep and dogs respectively and 376 tsetse flies (375 G. brevipalpis and 1 G. austeni) were also collected. PCR with universal KIN primers was used to detect the trypanosome parasites in both blood and tsetse flies. From 137 cattle samples 23.4% (32/137) were positive for the presence of trypanosome infections whilst none were positive for sheep, goat and dog samples. A total of 15.4% (54/375) G. brevipalpis tested positive for trypanosomes. Detected trypanosome species with KIN primers were Trypanosoma congolense (Savannah) and T. theileri for blood samples and for tsetse flies T. congolense (Savannah and Kilifi) types were detected. Nested PCR targeting 18S rRNA gene detected T. congolense (Savannah) and T. theileri species. The sequences from this gene revealed great genetic diversity within these Trypanosoma species. Amplification of gGAPDH gene detected T. congolense (Savannah) and T. brucei brucei species when subjected to BLAST. Sequences obtained from this gene also revealed great genetic diversity and showed that the detected trypanosomes are different genotypes from the known species in other countries outside South Africa. Phylogenetic analysis revealed that South African Trypanosoma species were more genetically related to east African trypanosomes however, they formed isolated clusters with each other indicating that indeed they are different genotypes from the trypanosome species on the NCBI database. Blood meal analysis showed that G. brevipalpis preferred to feed on small mammals, birds and humans in the absence of livestock or other large wild reservoir hosts. This study showed that there are active trypanosomes circulating amongst livestock and tsetse flies in KwaZulu-Natal Province as well as the prevalence of T. theileri and T. b. brucei which were never documented in previous studies. Further research is needed to investigate the pathogenicity of these detected Trypanosoma parasites in domestic animals.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2013
Keywords: Tsetse-flies -- South Africa -- KwaZulu-Natal; African trypanosomiasis -- South Africa -- KwaZulu-Natal; Insects as carriers of disease -- South Africa -- KwaZulu-Natal; Host preference; Phylogenetic position; Genetic diversity; Prevalence; PCR